THE ANALYSIS OF DERIVATIONAL AFFIXES IN COLLINS SCRABBLE WORDS 2021 (CSW21) - Agil Ramadhan Saputra; Franscy Franscy (Universitas Bandar Lampung, 2023)
This research is about the analysis of derivational affixes found in Collins Scrabble Words 2021. The research objectives of this research are to analyze the types and the meaning of the derivational affixes in Collins Scrabble Words 2021. The qualitative method which was an explanatory sequential design was used in conducting this research. The data source of this research is Collins Scrabble Words 2021. The data of this research is the words containing of derivational affixes where the maximal length is only 7 letters in 20 words of each alphabet. The results of the research showed that there are 457 words containing derivational affixes. There are 48 words attached with derivational prefixes, and 409 words attached with derivational suffixes. Prefixes found in Collins Scrabble Words 2021 arebi- (1), dis- (4), en- (6), fore- (1), il- (1), im- (1), mis- (5), out- (2), over- (2), pre- (2), sub- (3), un- (20). Meanwhile, the suffixes are –al (18), -ity (20), less-(10), -ify (19), -ly (87), -ize (7), -ism (2), -ic (17), -ee (12), –er (38), -ness (17), -or (5), -th (10), -hood (11), -y (58), -ous (27), -ful (11), -ish (1), -age (5), -able (9), -ure (1), -en (20), -ion (3), -ive (3), -ship (2), -tic (1), -ence (1), -ible (1), -ist (1), -ment (1), -ary (1). The derivational affixes functions consist of Verb Maker, Noun Maker, Adjective Maker, and Adverb Maker.